Translanguaging in The Indah G Show: Adultery, Infidelity and Homewrecking FT. Davina Karamoy of 'Ipar Adalah Maut' (Sastra Inggris UNPAM, 2025)
This study aims to analyse the types and function of translanguaging used in the conversation between Indah and Davina on the Indah's G show YouTube channel. In this study, the writer uses descriptive qualitative method to explain the data by following Garcia & Otheguy (2014) and Garcia & Otheguy (2015) the theory of translanguaging to answer the statement of problems. This study indentifies 21 the types of translanguaging: 6 basic words insertion, 1 invented words insertion, 6 loan words insertion, 6 phrase words insertion, 1 reduplication words insertionan, and 1 regional particle insertion. In addition, 2 influenced by cognitive function, 11 influenced by communicative function, 8 influenced by social or expressive functions. The data finding found that Indah is the dominant use the types of translanguaging during the conversation. As a result, Indah used translanguaging to be more communicative while discussing some of significant topics with Davina in the conversation.